Badis limaakumi, a new species of badid fish from Nagaland, Northeast India (Teleostei: Percomorpha: Badidae) - Praveenraj, Jayasimhan (Zootaxa, 2023)
Badis limaakumi, a new species of Badis from Nagaland, Northeast India is distinguished from all its congeners by the following combination of characters: a large (>60 mm SL) and slender body (23.2–28.0% of SL), presence of an opercular blotch at the base of the opercular spine, absence of blotches on the sides and fins, as well as on the cleithrum, and greater number of lateral-line scales.